1990
DOI: 10.1111/j.1365-2052.1990.tb03215.x
|View full text |Cite
|
Sign up to set email alerts
|

Two new sheep haemoglobins, one of which is replaced by haemoglobin C in anaemia

Abstract: Two new haemoglobin variants, provisionally named Hb G and Hb H, were found during a survey of 295 Welsh Mountain cross-bred sheep. Both haemoglobins appear to be beta chain variants controlled by genes allelic to those for the common forms Hb A and Hb B. Studies on an anaemic Hb AH and an Hb AG type sheep showed that Hb G, like Hb A, is replaced by Hb C in anaemia whereas Hb H, like Hb B, is not replaced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The HBX allele was added in the hemoglobin-b system tested. It is presumed that the hemoglobin-b component coded by this allele is electrophoretically similar to that of the HBH allele, which was reported by Kilgour et al (1990).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The HBX allele was added in the hemoglobin-b system tested. It is presumed that the hemoglobin-b component coded by this allele is electrophoretically similar to that of the HBH allele, which was reported by Kilgour et al (1990).…”
Section: Discussionmentioning
confidence: 83%
“…Polyacrylamide gradient gel electrophoresis was used for the transferrin system (Ghane et al, 1977), horizontal starch-gel electrophoresis for the arylesterase and X-protein systems (Tsunoda et al, 1984;Tucker et al, 1967), polyacrylamide-gel isoelectric focusing for the hemoglobin-b system (Kilgour et al, 1990), and an atomic absorption flame emission spectrophotometer (Shimazu, AA-6200) or compact ion densitometer (Horiba, Cardy Ion) for the potassium transport system. The staining procedures for detecting transferrin, hemoglobin-b, and X-protein components were conducted according to routine methods using Coomassie brilliant blue R-250 or G. Arylesterase activity was detected using a-naphthyl acetate as a substrate and fast blue RR salt as a dye.…”
Section: Protein and Nonprotein Phenotypingmentioning
confidence: 99%
“…Analysis of lysates of the Sardinian breeds by IEF indicated that one animal was of the Hb AA and 16 were of the Hb AB phenotype, the Figure 1 also indicates that the px chain has a different mobility from that of the PH, the latter being not separated with respect to the normal PB (Kilgour et al 1990). Application of lysates containing both the Hb B and Hb X to the urea polyacrylamide gel electrophoresis at alkaline pH, which allowed the PE chain to be separated from the pB (John & John 1977), resulted in a single @-chain band.…”
Section: G E N O M E Analysismentioning
confidence: 98%
“…In the present study, of all the enzymes used, DraI, EcoRI and BamHI proved to be even more informative in giving rise to GSHP. Hb C is produced under anaemia conditions only by sheep of the Hb A type (van Vliet & Huisman 1964) as is the case of the Hb G (Kilgour et al 1990). As expected, the pattern was found to be distinctly different in all the species compared with cow and buffalo genomes.…”
Section: G E N O M E Analysismentioning
confidence: 99%
“…Polyacrylamide gradient gel electrophoresis was used for the transferrin system (Ghane et al 1977), horizontal starch-gel electrophoresis for the arylesterase and X-protein systems (Tsunoda et al 1984;Tucker et al 1967), polyacrylamide gel isoelectric focusing for the hemoglobin-b system (Kilgour et al 1990), and a compact ion densitometer (Horiba, Cardy Ion) for the potassium transport system. The staining procedures for detecting transferrin, hemoglobin-b, and X-protein components were conducted according to routine methods using Coomassie brilliant blue R-250 or G. Arylesterase activity was detected using a-naphthyl acetate as a substrate and fast blue RR salt as a dye.…”
Section: Protein and Nonprotein Phenotypingmentioning
confidence: 99%